ROTATING CURVE OF THE GALAXY NGC 1068 - E.K. Denissyuk; R.R. Valiullin (Academic Scientific Journal of Computer Science, 2019)
The matter in the body of spiral galaxies (stars, nebulae, clusters), judging by their images, is distributed very non-uniformly. Moreover, all objects have their own velocities in space. However, in general, they are affected by the gravitational field of the total mass, referred to the center of the galaxy. One of the main aim is to evaluate this mass. In order to weaken the effect of random velocities, the average spectrum from fairly large sections of the galaxy along the entrance slit of the spectrograph is recorded. In the Fesenkov Astrophysical Institute (FAPHI) the spectral observations of the bright Seyfert galaxy NGC 1068 were carried out in the red region of the spectrum. The telescope AZT-8 with a diameter of 0.7 m and a slit spectrograph designed and manufactured in FAPHI was used. The spectra were recorded on a SBIG CCD ST-8 (1530x1020, 9μ). The spectrograms obtained with the long slit were used to measure the profiles of the Hα and [NII], 6583Ǻ, emission lines, namely, the radial velocities were determined at different distances from the center in the 9 "x10" areas. Further processing assumes that the galaxy is a thin circular disk whose matter rotates around the center so that at each distance from the center the rotation velocity is constant and it depends only on the distance to the center, and the disk itself is observed as an ellipse due to the inclination to the line of sight. In order to obtain a real dependence of the rotational velocities on the distance from the center under these assumptions, it is necessary to translate the distances along the slit and the radial velocities measured at these points into the galaxy plane by taking into account its inclination to the line of sight. As a result, the dependence of the rotation velocities of matter on the distance to the center was obtained. The mass of the disk with a radius of 6 parsec was estimated.